Clinical study on the effects of different cold compress methods and durations on postoperative complications following mandibular impacted third molar extraction - Xie, Zhiwen; Zhang, Wenjuan; Du, Tianxiang; Wang, Ying; Wang, Jiantao; Li, Jinlu; Qu, Pengfei (Frontiers in Surgery, 2025)
BackgroundTo optimize the postoperative cold compress protocol for mandibular impacted third molar extraction.MethodsSubjects were randomly divided into two major groups. The first group compared continuous vs. intermittent cold compress application, while the second group evaluated the duration of cold compress therapy. Postoperative outcomes, including pain intensity, facial swelling, trismus, and wound hemorrhage, were systematically analyzed.ResultsContinuous cold compress application within the first 6 h postoperatively demonstrated superior efficacy over intermittent application in alleviating pain, reducing swelling, improving mouth opening, and minimizing hemorrhage incidence. Cold compress application during postoperative D1 significantly controlled hemorrhage and mitigated acute pain. Prolonged therapy to D3 further enhanced facial edema reduction and trismus resolution.ConclusionsA protocol of continuous cold compress application for 6 h daily during the initial 3 postoperative days significantly reduces complications, offering optimal clinical outcomes.